On Randomly Perturbed Linear Oscillating Mechanical Systems - Skorokhod, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove that the amplitudes and the phases of eigenoscillations of a linear oscillating system perturbed by either a fast Markov process or a small Wiener process can be described asymptotically as a diffusion process whose generator is calculated.